Nasionalisme Dalam Tinjauan Islam - Ahmad Hanany Nasheh (Ulumuddin : Jurnal Ilmu-ilmu Keislaman, 2014)
In the global history of Islam as well as in its local context of Indonesia, the essence of nationalism is the willingness to unite as one nation in the political sense. This unity of the nation in the political sense will become much stronger when supported by factor of one religion, one language, and one race which is more prominent. But the fanatical nationalism without tolerance to underestimate religious values are certainly not in line with the values of Islam. Nationalism in the Islamic view is love and loyalty to the homeland that should not exceed the love and loyalty to Allah and His Messenger.